Senior Citizenâ€™s Understanding Regarding the Quality of Life and Policy of Bangladesh - Shamima Lasker; Turna Tribenee Mithila; Arif Hossain; Md Ruhul Amin (Journal of Mathematics Instruction, Social Research and Opinion, 2023)
Older people are encouraged to participate more in the economic, social, and governmental sectors as part of progressive aging policies worldwide. Very little is known about applying engagement techniques or carrying out strategies in Bangladesh that are important for involving seniors in social engagement. Therefore, this qualitative research was conducted in Dhaka, Bangladesh, among 385 people aged sixty or above to assess their understanding of the quality of life and the gap in government policy. Results showed that between 60 and 65 were more mobile, creative, engaged in productive activity, and had significantly higher decision-making power (p<0.000). Aging greatly enhances dependency (p<0.000). Lower-educated people were significantly dependent on their families (p<0.000). Moreover, elderly income and the cost of treatment were significantly correlated to abuse (p<0.001). Furthermore, 10% of participants reported negative relationships with family members (p<0.031).Â  However, most (61.6%) were unaware of the 2013 Parent's Care Act. Though most participants (73.2%) knew of the government-funded Old Age Allowance, 92.5% received no non-governmental assistance. The research concluded that education and economic condition have a long-term relationship with reducing dependency. In recommendation, Government can increase the retirement age from 59 to 65 years which may increase self of security, respect, and self-esteem and reduce harassment. Parent's Care Act 2013 should implement. Government should include Community Health and Social Service centers for the quality of life of the elderly.